Mozart's Così fan tutte - Da Ponte, Lorenzo, 1749-1838 (Opera classics library., 2005)
A comprehensive guide to Mozart's COSI FAN TUTTE, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 30 music highlight examples.